2000
DOI: 10.1097/00005392-200003000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Renal Tumors 4 Cm. Or Less in a Contemporary Cohort

Abstract: Patients with a small renal tumor have similar perioperative morbidity, pathological stage and outcome regardless of treatment with partial or radical nephrectomy. Therefore, partial nephrectomy remains a safe alternative for tumors of this size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
187
0
13

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(204 citation statements)
references
References 34 publications
4
187
0
13
Order By: Relevance
“…It has been demonstrated that both open and laparoscopic partial nephrectomy produce superior functional outcomes and oncologic outcomes that are at least equivalent to the outcomes produced after radical nephrectomy for selected tumors. 16,[19][20][21][22] Percutaneous tumor ablation and active surveillance are considered for patients who may be poor surgical candidates. Although it is not quite as effective as partial nephrectomy, approximately 80% of patients are disease-free after thermal ablation, and this remains a valid nephron-sparing intervention for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that both open and laparoscopic partial nephrectomy produce superior functional outcomes and oncologic outcomes that are at least equivalent to the outcomes produced after radical nephrectomy for selected tumors. 16,[19][20][21][22] Percutaneous tumor ablation and active surveillance are considered for patients who may be poor surgical candidates. Although it is not quite as effective as partial nephrectomy, approximately 80% of patients are disease-free after thermal ablation, and this remains a valid nephron-sparing intervention for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…2 Because of the small size and early stage of these tumours, surgeons are able to do partial nephrectomies without compromising safety and oncological efficacy. 3,4 In tertiary-care centres in the USA, partial nephrectomy now accounts for 30-65% of all surgical procedures for renal cortical tumours. 5-7 However, this trend does not represent current US surgical practice for renal cortical tumours.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4,11,12 In synchronicity with the gradual dissemination of laparoscopic radical nephrectomy, 2,4 multiple investigators reported that, for selected patients with smaller renal tumors, partial nephrectomy yields oncologic outcomes that are indistinguishable from the outcomes achieved by radical excision. [13][14][15] Partial nephrectomy also preserves long-term renal function 16,17 while reducing over-treatment of patients with benign 18 or clinically indolent 19 tumors.…”
mentioning
confidence: 99%